(untitled) - Overman, Larry E. (New York, 2002)
Organic Reactions is a comprehensive series of volumes composed of chapters devoted to important synthetic reactions. The subjects are presented from the preparative viewpoint and particular attention is given to limitation, interfering influences, effects of structure, and the selection of experimental techniques.
Keywords: Chemistry, organic,Chemical reactions,Organic compounds; Synthesis